Exploring Strategic Management and Co-Creation in the World: A Bibliometric Review from Scopus Database Journal - Heryani, Yani; Triansyah, Fadli Agus; Wibowo, Lili Adi; Junia, Annisa Aghniarahma; Lizein, Baandaalr; Inomjon, Qudratov (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
In the contemporary age of globalization, business and industry are experiencing dynamic and rapid changes. Strategic management and co-creation are a critical approach to management that combines business strategy with active stakeholder collaboration to create added value and competitive advantage. This study investigates developments in the literature related to the topic "Strategic Management and Co-Creation" using bibliometric analysis from 2007-2023 using 315 documents from the Scopus database. This study examines publication trends in Strategic Management and Co-Creation from 2007 to 2023. The results show a significant increase in publications, peaking in 2022. Key journals that dominate publications include Sustainability Switzerland, Journal of Business and Industrial Marketing, and Journal of Business Research. The main fields of study are business, management, accounting, and social sciences. This research demonstrates the significant developments in Strategic Management and Co-Creation with broad and diverse contributions from different authors, institutions, and countries. It overviews how far this topic has developed and how contributions from various sources and disciplines have shaped a richer understanding of Strategic Management and Co-Creation in multiple contexts. Keywords: Strategic management, Co-creation, Bibliometric, Scopus journal